A prática da leitura de poesia para a formação humana e crítica do aluno no ensino médio - Ribeiro, Cleunice Terezinha da Silva (2015)
This dissertation is a study about the poetry reading contribution to human and critical development of high school’s students. The research subject is poetry reading of two modern poets and two contemporary writers, as follows: Carlos Drummond de Andrade, Manuel Bandeira, José Paulo Paes and Paul Leminski. This research discusses the role of poetry in the classroom, considering the educational process of literary reading, as wells as it investigates how the poetry of these poets can contribute to human development and critical students in high school. The implementation of the work follows the guidances of Bordini and Aguiar Recepcional Method (1993), with questionnaires, poetry analysis (didactic sequence), essay productions and a reading memorial construction. The research questions include the investigation of theoretical texts and official documents that deal with themes about poetry and humanization, poetry and criticism. In order to achieve this, it was recruited as a theoretical approach Jorge Larrosa (2000), Antonio Candido (2004), Todorov (2009), Octavio Paz (1993); and documents Education Law (Lei de Diretrizes e Bases da Educação Nacional LDBEN, 1996); Parâmetros Curriculares Nacionais (PCNs, 1999); Orientações Curriculares para o Ensino Médio (OCPEM, 2006), among others. The conclusions of this study point to the poetry reading mediation in the classroom and the critical and human development.